Relationship between social anxiety and separation anxiety symptoms with insistence on sameness with the mediating role of sensory hypersensitivity - Shima Keshavarz; Khalil Esmaeilpour (BMC Psychology)
Abstract Background Autism spectrum disorder (ASD) is characterized by impairments in social communication and interaction, restricted and repetitive patterns of behavior, and sensory processing abnormalities. These core features are often accompanied by comorbid anxiety disorders. However, the sequence and mechanisms of these associations warrant further investigation. Therefore, the aim of this study was to examine the relationship of social anxiety and separation anxiety on insistence on sameness, mediated by sensory hypersensitivity. Methods This was a cross-sectional study based on caregiver reports of 247 children, aged 7 ̶ 11 years. The parents completed the Autism Quotient-Children’s Version (AQ-C), the Repetitive Behavior Questionnaire-2 (RBQ-2), the Sensory Profile 2 (SP2), and the Spence Children’s Anxiety Scale-Parent Version (SCAS-P). Results The path analysis revealed a significant indirect effect of social anxiety and separation anxiety on insistence on sameness via sensory hypersensitivity (p ≤ 0.05). However, neither social anxiety nor separation anxiety had a significant direct effect on insistence on sameness (p = 0.108 and p = 0.342, respectively). Conclusions Based on the results, the mediated association of sensory hypersensitivity with the relationship between social anxiety, separation anxiety, and insistence on sameness was observed. The article discusses the theoretical explanations and implications of the results, as well as various manifestations of anxiety symptoms in children with ASD.